Vegetables Consumption and its Benefits on Diabetes - Carlos da Silva Dias, João; Imai, Saeko (Journal of Nutritional Therapeutics, 2017)
Vegetables are indispensable for equilibrated diets since they charge dietary fiber, phytochemicals, vitamins, and minerals. Each vegetable comprise a distinct amalgam and amount of these compounds, which differentiate them from other vegetables. Vegetable intakes has been highly correlated with improved gastrointestinal health, reduced risk of heart attack, some types of cancer and chronic ailments such as diabetes. Type 2 diabetes is a lifestyle ailment. Our vegetables selection and amount of dietary fiber, phytochemicals, vitamins and minerals consumed can either prevent or promote diabetes. This article highlights the nutritional and health benefits of different vegetables and their dietary fiber, vitamin C, vitamin E, carotenoids, flavonoids, thiosulfides, magnesium, selenium, chromium, and zinc contents, to prevent and reverse diabetes. The proper order of eating vegetables before carbohydrate and its effect on postprandial blood glucose levels, and glycemic control is also discussed. Data shows that eating vegetables before carbohydrates is effective to reduce postprandial hyperglycemia in Type 2 diabetes patients, as well as in healthy people. So vegetables should be eaten before carbohydrates at every meal